TASK-BASED ACTIVITIES WITH CHARACTER VALUES FOR TEACHING ENGLISH LITERACY OF 2ND GRADE STUDENTS IN NBBS - ., Gina Wulandari; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Dewasa ini, guru-guru di Indonesia dihadapkan dengan dua masalah utama dalam pengajaran yaitu bagaimana mengajarkan Bahasa Inggris secara kontekstual dan inovatif, serta bagaimana menyisipkan pendidikan karakter sebagai aturan dari pemenrintah untuk meningkatkan moral dari generasi muda. Penelitian ini bertujuan untuk menganalisis jenis-jenis aktivitas berbasis tugas dengan nilai-nilai karakter untuk mengajarkan literasi Bahasa Inggris di sekolah dasar. Penelitian ini dilaksanakan dalam bentuk deskriptif kualitatif dengan analisis data triangulasi. Subyek penelitian ini adalah siswa kelas 2 sekolah dasar North Bali Bilingual School Singaraja selama satu semester di tahun 2014. Berdasarkan observasi, ada sebelas jenis aktivitas berbasis tugas yang ditemukan diantaranya: take-home reading task, reading buddy, collaborative literacy task, scavenger hunt, door’s decoration, daily task, spelling quiz, super reader challenge, earth day celebration, and reading world day celebration (yang berisi 3 kegiatan literasi Bahasa Inggris). Hasil dari penelitian ini menunjukkan bahwa aktivitas-aktivitas tersebut bisa membuat siswa fokus terlibat dalam proses belajar dan membuat siswa termotivasi untuk mempelajari Bahasa Inggris.Kata Kunci : aktivitas berbasis tugas, nilai karakter, literasi Bahasa Inggris Nowadays, teachers in Indonesia are faced with two main problems of teaching such as how to teach English contextually and innovatively, and how to insert character education as the government’s policy to improve the morality of the young generations. This study aimed to analyze kinds of task-based activities inserted with character values in teaching English literacy in elementary school. The study was conducted in descriptive qualitative study with the triangulation data analysis. The subject of the study was on grade 2 students of North Bali Bilingual School Singaraja for about one semester in 2014. Based on the observation, there were about eleven task based activities documented such as: take-home reading task, reading buddy, collaborative literacy task, scavenger hunt, door’s decoration, daily task, spelling quiz, super reader challenge, earth day celebration, and reading world day celebration (consisted of 3 literacy activities). The result of the study stated that the activities can make students on task during the teaching learning process and make students highly motivated to learn English.keyword : task-based activities, character values, English literacy